Quantum size effect and interlayer electron tunneling in metal-semiconductor superlattices: Электpонные свойства металлов и сплавов - Shekhter, N. Ya. Fogel,R. I.; Slutskin, A. A.; Fogel, N. Ya.; Slutskin, H. A. Kovtun,A. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
A new type of quantum size effect in metal-semiconductor superlattices is predicted. Giant oscillations of the transverse tunnel conductivity arise if size quantization of the electron spectrum in the metal layers takes place. This effect is due to the fact that the probability of metal electron tunneling through a semiconductor layer depends sharply on the electron incidence angle. The oscillations have been found to exist even in disordered systems, provided the electrons in metal layers undergo low-angle scattering on imperfections.